A quartz resonator force transducer - WERESZKO, M. (Archives of Acoustics, 1991)
The prototype of force transducer with the AT-cut quartz resonator serving as the sensitive to force element is described. The operating principle of this transducer is based on the relation between the resonator vibration frequency and the force acting on this resonator. Since the quartz resonator is sensitive to ambient temperature, the force transducer has been also equipped by the LC-cut resonator, which plays the role of temperature sensor with frequency output signal. This signal is used to compensate the thermal influences.